HPLC characterization of molluscicidal component of Tamarindus indica and its mode of action on nervous tissue of Lymnaea acuminata - Neelam Soni (Journal of Ayurveda and Integrative Medicine, 2020)
Background: Fasciolosis is a water-borne disease with gastropods snail (Lymnaea acuminata) act as key-link is still burden for mankind especially in developing countries. Snail control is one of the important tools to trim down the frequency of fasciolosis. Objective: To evaluate the toxic effect and inhibitory potential of plant Tamarindus indica and their active constituent on the key enzyme of nervous tissue of snail L. acuminata. Method: The present study deals with the chromatographic isolation and identification of molluscicidal component from Tamarindus indica bark and its effects on enzymes activities of vector snail L. acuminata. Result: The toxicity study reveals that among all organic extract ethanol extract of T. indica bark (96 h LC50:127.4 mgL−1) was more effective than other organic extracts. The 96 h LC50 of column purified fraction of T. indica bark was 13.78 mgL−1 respectively. Saponin was isolated, characterized and identified as active molluscicidal component in the bark of T. indica by column chromatography, TLC and HPLC chromatographic methods. The in vivo and in vitro treatment of column purified fraction and saponin has significant inhibition in enzyme AChE, ACP and ALP activities. The study of inhibition kinetics indicates that inhibition of AChE and ALP is competitive, while ACP is uncompetitive in both the treatments. Conclusion: Thus inhibition of these enzyme activities by T. indica bark column purified fraction and saponin in the snail L. acuminata may be the cause of its molluscicidal activity which leads snail death.